A retrospective analysis of severe asthma treatment with Mepolizumab - Mattia Serao; Rossana Vigliarolo; Tiziana Trequattrini; Angela Succu; Marianna Lilli; Rosario Rivitti; Aldo Ciani; Giulia Cacciani; Sara Mannucci; Maria Cristina Zappa (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2019)
Among the different types of bronchial asthma, the allergic one is certainly the most easily found. Allergic asthma is characterized by the presence of IgE antibodies called "reagine", responsible for triggering respiratory allergic crises in the presence of perennial or seasonal specifi c allergens. Allergic asthma with severe and persistent symptoms, with high levels of circulating IgE, can be treated with Omalizumab, a humanized monoclonal antibody obtained from recombinant DNA.